Transformational Experiences. The Role of Immersive Arts and Media in Individual and Societal Change (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2025)
We live in times of humanitarian and environmental crises. The effects of climate change add to the economic, physical, and mental suffering caused by social discrimination, in the form of gender, class, and race inequalities.Encounters with and creation of arts have been suggested as a potential remedy, allowing to stay with the trouble rather than running from it, and imagining a different future rather than manifesting the past. But what are the concrete chances that all this really happens?Similar questions can be raised in relation to immersive media. The latter have been claimed to possess an unprecedented prosocial potential. However, what are the appropriate strategies to ensure that such potential is actually expressed?For this issue of AN-ICON. Studies in Environmental Images, we selected diverse contributions investigating the role of the arts and media in rethinking (and acting upon) societal and environmental problems, focussing on immersive experiences in particular.
Keywords: Virtual reality; Contemporary art; Discrimination; Climate change; Attitude change